231k views
3 votes
Factor 6x4 – 5x2 + 12x2 – 10 by grouping. What is the resulting expression?

User Brayn
by
5.3k points

2 Answers

3 votes

Answer:

(x^2 + 2)(6x^2 – 5)

Explanation:

6x^4 – 5x^2 + 12x^2 – 10

=(6x^4 – 5x^2) + (12x^2 – 10)

=x^2 (6x^2 – 5) + 2(6x^2 – 5)

=(x^2 + 2)(6x^2 – 5)

Answer

(x^2 + 2) and (6x^2 – 5) are factors of the expression 6x^4 – 5x^2 + 12x^2 – 10

User Deneen
by
4.9k points
3 votes

Answer:

(6x² - 5)(x² + 2)

Explanation:

Given

6
x^(4) - 5x² + 12x² - 10 ( factor the first/second and third/fourth terms )

= x²(6x² - 5) + 2(6x² - 5) ← factor out (6x² - 5) from each term

= (6x² - 5)(x² + 2)

User Marksl
by
5.1k points